1998
DOI: 10.1074/jbc.273.50.33595
|View full text |Cite
|
Sign up to set email alerts
|

Key Residues Characteristic of GATA N-fingers Are Recognized By FOG

Abstract: Protein-protein interactions play significant roles in the control of gene expression. These interactions often occur between small, discrete domains within different transcription factors. In particular, zinc fingers, usually regarded as DNA-binding domains, are now also known to be involved in mediating contacts between proteins. We have investigated the interaction between the erythroid transcription factor GATA-1 and its partner, the 9 zinc finger protein, FOG (Friend Of GATA). We demonstrate that this int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 55 publications
4
87
0
Order By: Relevance
“…The residues in the tail of the N finger appear to be crucial for its interaction with Fli-1. These residues differ from those required for the interaction with GATA-1's cofactor FOG, which is mediated through the residues within the core of the N finger itself and not the tail (11). Previous studies (12) have suggested that FOG might tether to a number of Ets factors (including Fli-1, Ets-1, and PU.1) to mediate the expression of the GPIIb gene.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The residues in the tail of the N finger appear to be crucial for its interaction with Fli-1. These residues differ from those required for the interaction with GATA-1's cofactor FOG, which is mediated through the residues within the core of the N finger itself and not the tail (11). Previous studies (12) have suggested that FOG might tether to a number of Ets factors (including Fli-1, Ets-1, and PU.1) to mediate the expression of the GPIIb gene.…”
Section: Discussionmentioning
confidence: 97%
“…The inserts were digested with EcoRI and SalI and subcloned into the same sites of pGexJT. The GST-mGATA-1 and pRcCMVmGATA-1 constructs used have been described previously (11,23). The GPIX-567 luciferase reporter construct has also been published previously (9).…”
Section: Methodsmentioning
confidence: 99%
“…The 3D structure of A201 to P240 of human and mouse GATA1 is displayed as a ribbon (pink); the zinc atom is displayed as an orange sphere. The positions of the zinc-chelating Cys residues on the ribbon are indicated in yellow; the positions of residues involved in the interaction with FOG-1 are in blue (23). Side chains are shown for the residues mutated in patients.…”
Section: Gata1 Mutations In Human Diseasementioning
confidence: 99%
“…The recent finding that the GATA-1 cofactor Friend of GATA (FOG) is required for the development of the thrombocytic lineage at a very early stage (Tsang et al 1998) led us to examine the role of FOG in the generation of MEPs and their differentiation. The FOG protein contains nine zinc fingers, at least two of which are capable of binding to the aminoterminal zinc finger (NF) of GATA-1 (Tsang et al 1997;Fox et al 1998Fox et al , 1999Crispino et al 1999). This interaction is necessary for the ability of GATA-1 to promote terminal erythroid differentiation (Crispino et al 1999), and GATA-1 and FOG cooperate to induce a megakaryocytic phenotype in the 416B myeloid cell line (Tsang et al 1997).…”
mentioning
confidence: 99%